ANALISIS SEMIOTIKA LOGO PARTAI NASDEM DALAM TAYANGAN IKLAN LAYANAN MASYARAKAT DI MNC TV - Dibya, Indra (Universitas Prof. Dr. Moestopo (Beragama), 2013)
Nowadays more and more community organizations (CBOs), and political parties are becoming more and moreevolved in our country because of the effect or fruit of freedom of democracy in Indonesia since the new orderof leadership patterns. Election as party logos popping up but most of the audience we do not know the symbolor logo of the latest party and community organizations who are now frequently made splashy electronic media.Among other organization that is now growing as the national Democratic Party evolved into a political partyNasdem, with Surya Paloh as chairman of the party is, and television media menggunakkan MNC as a TV adcampaign. Introduce logo mission vision Nasdem Party party.Logos such as clothes, profession, social status, logo can be interpreted (semiotics) as the identity of a personor organization, symbolize or depict ideological, vision and mission of an organization or party.